Self-medication practice among final year students of a governmental university: a comparison between medical and non-medical students - Akkawi, Muhammad Eid; Fata Nahas, Abdul Rahman; Alshami, Abdulkareem Mohammed (2020)
ntroduction: Self-medication is defined as any usage of the medications without having any proper diagnosis, consultation and prescription from a healthcare practitioner. Objective: This study aimed to determine the prevalence and pattern of selfmedication among undergraduate final year students, and to compare the prevalence and pattern of self-medication between medical and non-medical final year students. Method: A cross-sectional study was conducted among final year students (4 medical programmes and 1 non-medical programme) from International Islamic University Malaysia, Kuantan Campus. A pre-validated questionnaire was distributed to 300 students in October 2016. Chi-square test was used to compare between medical and non-medical students. Results: 225 medical and 63 non-medical students (science programme students) answered the questionnaire. The mean age was 23.23 0.733 years. More than half of the participants (61%) practiced self-medication with no significant difference between medical and nonmedical students (60.9% Vs 61.9%; P = 0.884). The most common reasons of selfmedication in both groups was “a previous experience with similar problem”; with fever being the most self-treated condition followed by flu/cold. The majority of both groups (89.9%; 92.1%) acknowledged the necessity of consulting a certified medical practitioner before taking any medications. However, only 69.3% of the non-medical students believed that selfmedication could be harmful compared with 89.3% of the medical students (P < 0.001). Conclusion: The prevalence of self-medication practice among medical and nonmedical students was high and there was also a lack of awareness about its harm among non-medical students.